1997
DOI: 10.1161/01.hyp.30.5.1085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sympathectomy on Mechanical Properties of Common Carotid and Femoral Arteries

Abstract: Sympathetic stimulation is accompanied by a reduction of arterial distensibility, but whether and to what extent elastic and muscle-type arterial mechanics is under tonic sympathetic restraint is not known. We addressed this issue by measuring, in the anesthetized rat, the diameters of the common carotid and femoral arteries with an echo-Doppler device (NIUS 01). Blood pressure was measured by a catheter inserted contralaterally and symmetrically to the vessel where the diameter was measured. Arterial distensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 18 publications
7
58
0
Order By: Relevance
“…These data suggest that modification of vascular compliance may be an important target of sympathetically mediated ␣ 1 -adrenergic stimulation. This observation is in agreement with previous studies that have found sympathetically mediated changes in vascular compliance, independent of diameter, in conduit vessels (11,61,76,86). Alternatively, the greater reduction in HR observed in PEvs.…”
Section: Discussionsupporting
confidence: 93%
“…These data suggest that modification of vascular compliance may be an important target of sympathetically mediated ␣ 1 -adrenergic stimulation. This observation is in agreement with previous studies that have found sympathetically mediated changes in vascular compliance, independent of diameter, in conduit vessels (11,61,76,86). Alternatively, the greater reduction in HR observed in PEvs.…”
Section: Discussionsupporting
confidence: 93%
“…21 At the opposite end of the baroreflex arc, norepinephrine affects arterial distensibility of the carotid sinus and aorta, altering discharge of the baroreceptor organs. 22 In the present study, baroreflex function significantly improved after successful reperfusion without significant alterations in serum norepinephrine concentrations. Therefore, it is unlikely that baroreflex impairment is primarily caused by sympathetic overactivity.…”
Section: Norepinephrine Concentrations and Baroreflex In Acute MIsupporting
confidence: 57%
“…45 Two, we have shown in rats that carotid and femoral artery distensibility is increased by sympathectomy. 46 We have shown that this is also the case in humans in whom radial artery and femoral artery distensibilities were found to increase markedly after removal of adrenergic tone by anesthesia of the brachial plexus and the spinal cord, respectively. 47 This is presumably due to a sympathetically mediated contraction of vascular smooth muscle, because contracted muscle tissue is less prone to distension for intravascular pressure than is muscle tissue in a relaxed state.…”
Section: Sympathetic Activation and Organ Damagementioning
confidence: 65%